An Overview of Knowledge and Attitude About Premenstrual Syndrome on 9th Grade Students at Junior High School Number 1 West Selemadeg - Ni Luh Ayu Radhaningsih; Ni Made Dwi Mahayati; Gusti Ayu Tirtawati (Fakultas Kebidanan Institut Kesehatan Medistra Lubuk Pakam, 2024)
Adolescent health efforts are activities that aim to help adolscents become healthy adults. The change towards adolescence is marked by puberty, such as the occurrence of menstruation in teenage girls. Before expriencing the menstrual phase, woman will experience symptoms such as stomach ache, difficulty concentrating and sharp emotional changes called premenstrual syndrome. The aim of this research is to determine the description of knowledge and attitudes about premenstrual syndrome in class IX students at SMP Negeri 1 Selemadeg Barat. This research wa conducted from March to April 2024 at SMP Negeri 1 Selemadeg Barat. This type of research is descriptive research with design cross sectional. The number of respondents used was 64 female students. Data collection includes filling out knowledge and attitudequestionnaires. The results of the study showed that the majority of respondents ages 15 years, began to experience menarche at the age of 12, has no sisters and the majority obtains information from the surrounding environment. The assessment regarding female students’ knowledge obtained results, only a few got good marks, namely 10 female students (15,6%) and the majority of female students showed a positive attitude, namely 36 female students (56,25%). Female students are advised to learn more about premenstrual syndrome and local health center staff are advised to provide edication to female students to from an attitude of students who are ready to face the problem menarche and premenstrual syndrome.